Learning bi-utterance for multi-turn response selection in retrieval-based chatbots. (16th April 2019) - Wang, Shuliang; Li, Dapeng; Geng, Jing; Yang, Longxing; Dai, Tianru
Multi-turn response selection is essential to retrieval-based chatbots. The task requires multi-turn response selection model to match a response candidate with a conversation context. Existing methods may lose relationship features in the context. In this article, we propose an improved method that extends the learning granularity of the multi-turn response selection model to enhance the model's ability to learn relationship features of utterances in the context, which is a key to understand a conversation context for multi-turn response selection in retrieval-based chatbots. The experimental results show that our proposed method significantly improves sequential matching network for multi-turn response selection in retrieval-based chatbots.